2006
DOI: 10.1007/s11270-006-9253-4
|View full text |Cite
|
Sign up to set email alerts
|

The Control of a Small Dam in Nutrient Inputs to a Hypertrophic Estuary in a Mediterranean Climate

Abstract: A two-year study was carried out in the lower part of the Palmones River to describe the role of a small dam controlling the nutrient fluxes to the estuary. Results showed an important spatial heterogeneity in the nutrient content and water properties of lowland catchment due to the effects of the small dam and the effluents of a sewage treatment work. Taking into account the values of hydraulic retention time, the dam could be considered as an optimally dimensioned pre-dam. Therefore, it removed on average mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Nitrogenous DOM is expected to follow complex dynamics. In situ processes such as phytoplankton uptake, mineralization and nitrification has been observed in other Mediterranean catchments (Lolite-Herera et al, 2009;Aviles & Niell, 2007), whereas DON ammonification by bacteria and subsequent nitrification of the released ammonium in freshwater systems have been discussed in a number of previous studies using incubation experiments (Selmer, 1998;Kerner & Spitzy, 2001;Badr et al, 2008). The exact mechanisms responsible for the observed distribution of DON in our study system cannot be identified from these data alone and additional process-focused experiments are needed to further resolve relative contributions of different processes in this system.…”
Section: In Situ Processesmentioning
confidence: 84%
“…Nitrogenous DOM is expected to follow complex dynamics. In situ processes such as phytoplankton uptake, mineralization and nitrification has been observed in other Mediterranean catchments (Lolite-Herera et al, 2009;Aviles & Niell, 2007), whereas DON ammonification by bacteria and subsequent nitrification of the released ammonium in freshwater systems have been discussed in a number of previous studies using incubation experiments (Selmer, 1998;Kerner & Spitzy, 2001;Badr et al, 2008). The exact mechanisms responsible for the observed distribution of DON in our study system cannot be identified from these data alone and additional process-focused experiments are needed to further resolve relative contributions of different processes in this system.…”
Section: In Situ Processesmentioning
confidence: 84%
“…The main sources of the dissolved silica present in surface waters are soil leaching and erosion, the impacts of agriculture and management being less marked than in the cases of nitrogen and phosphorus (Billen et al 1991;Anderson and Downing 2006;Avilés and Niell 2007). The DSi in aquatic ecosystems is taken up by siliceous phytoplankton, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the lower concentrations of DSi observed in the overlying water from Lake Daihai were attributed to the uptake and assimilation of diatom phytoplankton. Generally, the concentration levels and spatial distribution of DSi in overlying water are mainly regulated by soil leaching and erosion and rock weathering of the lake basin, rather than anthropogenic inputs (Anderson and Downing 2006;Avilés and Niell 2007). Thus, the high-concentration areas of DSi found in the northwestern and southern areas of Lake Daihai responded the influence of the main lake inlets (such as Yuanzi, Jiucai, Buliang, and Tiancheng Rivers) on DSi spatial distribution (Fig.…”
Section: Dsimentioning
confidence: 99%